Entrepreneurial inputs and outcomes new studies of entrepreneurship in the United States - Libecap, Gary D. (JAI, 2001)
The performance of economies depends upon entrepreneurship. Entrepreneurs identify new opportunities, implement new technologies, provide new products and services, and generally, make an economy vibrant. Yet, little is understood of the institutional structure that supports entrepreneurship or of the economic and sociological factors that encourage entrepreneurial activity. The papers in this volume represent research on these issues. The material is relevant for both an academic and lay audience. Three papers by Kortum and Lerner; Thomas; and Ziedonis and Hall examine the US patent system and its relationship to venture capital, its impact on R&D expenditures and access to new technologies, and its affect on "patent portfolio races." Two others by Prasad, Vozikis, and Bruton, and Quadrini address financing issues, including the importance of private savings by entrepreneurs for self financing of new ventures and for signaling venture quality. Quadrini shows that entrepreneurs experience greater upward mobility than do others in the population. A related paper by Lowe explores the role and experience of start-ups in commercializing university inventions, a growing source of new technology. Kerkvliet and Shogren examine innovation in the institutions used by firms to obtain productive inputs. Two other papers by Roberson-Saunders and Holcombe examine the characteristics of entrepreneurs and the importance of entrepreneurial activity in the economy in the generation of new products, processes, and services and outlines policies for encouraging entrepreneurship. This collection of papers highlights the variety of issues associated with gaining a better understanding of entrepreneurship.
Keywords: Entrepreneurship -- United States.; Entrepreneurship -- United States -- Finance.; Patents -- United States.; USA.; elektronické knihy; electronic books